2012
DOI: 10.1136/vr.100719
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterisation of quinolone resistance in Escherichia coli from animals in Turkey

Abstract: The aim of this study were to detect the gyrA, parC and marR mutations and qnr genes (qnrA, qnrB and qnrS) in 120 strains of Escherichia coli isolated from animals. European Committee on Antimicrobial Susceptibility Testing and Clinical Laboratory Standards Institute disc diffusion and minimum inhibitory concentration (MIC) tests, respectively, were used to determine fluoroquinolone (FQ) resistance, and molecular methods were used to detect the mutations and the genes. E coli isolates with an MIC of ≥8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…The qnrA, qnrB, qnrS, and aac(6')-Ib-cr genes are the most commonly identified resistance determinants in Turkey (Nazik et al 2009;Ozgumus et al 2009). The prevalence of qnr genes among the E. coli isolates obtained from animals in the EU and Turkey ranged between 3% and 15% (Veldman et al 2011;Cengiz et al 2012). In another study from Turkey, Nazik et al (2009) reported qnr genes in Enterobacter spp., E. coli and K. pneumoniae.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The qnrA, qnrB, qnrS, and aac(6')-Ib-cr genes are the most commonly identified resistance determinants in Turkey (Nazik et al 2009;Ozgumus et al 2009). The prevalence of qnr genes among the E. coli isolates obtained from animals in the EU and Turkey ranged between 3% and 15% (Veldman et al 2011;Cengiz et al 2012). In another study from Turkey, Nazik et al (2009) reported qnr genes in Enterobacter spp., E. coli and K. pneumoniae.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports in Turkey have evaluated the plasmid-mediated quinolone resistant (PMQR) in animal isolates of Escherichia coli strains (Cengiz et al 2012;Mustak et al 2012). However, this study is the first and unique one investigating the PMQR determinants of Salmonella isolated from chicken carcasses in Turkey.…”
mentioning
confidence: 99%
“…The prevalence of pathogenic E. coli in food isolates is low, compared to animal isolates and clinical infections (23). The prevalence of commensal E. coli isolates from food has been extensively studied in developed countries (24) but little research has been conducted in Turkey (25).…”
Section: Resultsmentioning
confidence: 99%
“…Compared to our study (4.08%), the observed resistances of food originated E. coli isolates to ciprofloxacin were much higher; 31.9% and 31.1%, respectively from other studies (Arslan and Eyi 2011;Gundogan and Avci, 2013). However, the few most recent studies from Turkey focused on fluoroquinolones (ciprofloxacin) resistant E. coli isolated from animals (Cengiz et al, 2012;Mustak et al, 2012) and reported that 47 (50.0%) of 94 chicken, 3 (4.5%) of 66 sheep, 5 (9.6%) of 52 cattle and 3 (6.4%) of 47 dog E. coli strains were found to be resistant to ciprofloxacin. In contrast to that study, a low level of ciprofloxacin resistance (9.52%) detected in the present study for sheep isolates.…”
Section: Discussionmentioning
confidence: 99%